Regulatory Focus, Motivation, and Their Relationship With Creativity Among Adolescents - Wang, Ling; Cui, Yue; Wang, Xinjing; Wang, Jin; Du, Kaiye; Luo, Zheng (Frontiers in Psychology, 2021)
Due to the close relationship among intrinsic/extrinsic motivation, regulatory focus, and creativity revealed by previous literature, intrinsic/extrinsic motivation may play a mediating role between regulatory focus and creativity. Therefore, the present study aimed to investigate the relationship between regulatory focus and creativity by combining intrinsic/extrinsic motivation. In this study, senior high school students (n = 418) completed the Regulatory Focus Questionnaire, the Working Preference Inventory, the Williams Creativity Assessment Packet, and the Kirton Adaption-Innovation Inventory. The correlation analysis showed that both promotion and prevention focus positively correlated with intrinsic motivation; intrinsic motivation and promotion focus positively correlated with creativity personality and innovative-adaptive cognitive style; and extrinsic motivation and prevention focus negatively correlated with innovative-adaptive cognitive style. Furthermore, a path model showed that promotion focus positively predicted creativity through the mediation of intrinsic motivation. In general, our study suggests that intrinsic motivation plays a mediating role between promotion focus and creativity. Our results complement those of previous studies and serve as inspiration for the cultivation of creativity in classroom or enterprise settings.